Rhodium-Phosphite SILP Catalysis for the Highly Selective Hydroformylation of Mixed C4 Feedstocks - Jakuttis, Michael; Schönweiz, Andreas; Werner, Sebastian; Franke, Robert; Wiese, Klaus-Diether; Haumann, Marco; Wasserscheid, Peter (Angewandte Chemie International Edition, 2011)
The cat. that got the butene: Highly active and selective diphosphite ligands are applied for rhodium-catalyzed supported ionic liquid phase (SILP) hydroformylation and make it possible to form linear n-pentanal with exceptional selectivity from a mixed butene feedstock by combined isomerization and hydroformylation (see picture, vials 1–4 show typical SILP catalysts employed in this study.). The SILP catalyst is stable for more than 800h on stream.